2019
DOI: 10.1037/xlm0000605
|View full text |Cite
|
Sign up to set email alerts
|

Item-to-item associations in typing: Evidence from spin list sequence learning.

Abstract: Associations are formed among the items in a sequence over the course of learning, but these item-to-item associations are not sufficient to reproduce the order of the sequence (Lashley, 1951). Contemporary theories of serial order tend to omit these associations entirely. The current paper investigates whether item-to-item associations play a role in serial order, specifically focusing on whether these associations influence how typists order their keystrokes. To address this question, participants completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Strong evidence for associations between items has been found using the spin-list paradigm (Kahana et al, 2010;Lindsey & Logan, 2019, 2021. In this paradigm, participants initially study a list of items such as ABCDEF G. In the spin-list condition, on subsequent trials participants study a rotated, or "spun" list of the same items, such as DEF GABC, whereas in the control-list condition participants study the same list without variation in its starting position.…”
Section: Is There Evidence For Associations Between Items?mentioning
confidence: 99%
See 1 more Smart Citation
“…Strong evidence for associations between items has been found using the spin-list paradigm (Kahana et al, 2010;Lindsey & Logan, 2019, 2021. In this paradigm, participants initially study a list of items such as ABCDEF G. In the spin-list condition, on subsequent trials participants study a rotated, or "spun" list of the same items, such as DEF GABC, whereas in the control-list condition participants study the same list without variation in its starting position.…”
Section: Is There Evidence For Associations Between Items?mentioning
confidence: 99%
“…Strong evidence for associations between items has been found using the spin-list paradigm (Kahana et al, 2010;Lindsey & Logan, 2019, 2021. In this paradigm, participants initially study a list of items such as ABCDEFG.…”
Section: Figure 16mentioning
confidence: 99%
“…Motor chunks would include only a limited number of responses (Abrahamse et al, 2013;Verwey, 2001), but multiple studies have shown that the indications for segmentation of longer sequences vanish with extended practice (Acuna et al, 2014;Ramkumar et al, 2016;Wymbs et al, 2012). This suggests that sequence learning at the motor level is based on response-response associations that do not impose a length restriction (Lindsey & Logan, 2019;Logan, 2020). This explains findings that the execution rate of individual responses of a well-known motor sequence increase with 1 Verbal knowledge may develop after executing keying sequences in the DSP task, but verbal coding may also precede the execution of these motor sequences (De Kleine & Verwey, 2009;Verwey, Lammens, & van Honk, 2002), like when learning to type in one's ATM pin number on a keyboard with an unfamiliar layout (Krakauer, Hadjiosif, Xu, Wong, & Haith, 2019;Verwey, 2015).…”
Section: Discrete Motor Sequences and C-smbmentioning
confidence: 99%
“…Second, we investigated the nature of the CI effect in that RP may benefit 2 Central-symbolic and sequential motor representations may well be based on the same associative chaining mechanism. This consists of associations developing between low-level representations that are repeatedly active at the same time (Abrahamse, JimĂ©nez, Verwey, & Clegg, 2010;Lindsey & Logan, 2019;MacKay, 1982MacKay, , 1990. There is now extensive neural evidence that associative learning is a general learning mechanism that occurs in sensory and motor neural systems (Beukema & Verstynen, 2018;Meyer & Olson, 2011;Mushiake, Inase, & Tanji, 1991) and in perception, memory, and action (Logan, 2020).…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation